Pembuatan Desain Kemasan untuk Usaha Mikro Kecil dan Menengah Melalui Strategi Virtual Marketing - Febriana, Widia; Sumadewa, I Nyoman Yoga; Satria, Christofer; Hasbullah, Hasbullah; Cahyadi, Irwan (LPPM Universitas Bumigora, 2024)
Micro, Small and Medium Enterprises (MSMEs) are the driving force of the economy that is expected to improve people's welfare. Community creativity and the ability to utilize existing natural resources to guide ideas and creations are realized in various MSME products. The purpose of this service program is to make existing product packaging designs, the work of the Central Lombok community, besides that we also provide assistance and training on how to market MSME products in Sintung village, Central Lombok Regency through virtual marketing strategies. The method used in this service is by identifying problems (mapping) offline; identifying problems from each MSME using indicators that have been determined by Bumigora University lecturers who carry out community service activities in Sintung Village. As a result of this community service, MSME communities are able to protect products to keep them good, clean, neat, and durable. Able to be an attraction for customers to recognize products and buy them. Able to create a positive image (image) about the product or company that produces